2023
DOI: 10.29333/ejmste/13658
|View full text |Cite
|
Sign up to set email alerts
|

Calculus instructors’ perspectives on effective instructional approaches in the teaching of related rates problems

Thembinkosi Peter Mkhatshwa

Abstract: Much research has reported on students’ difficulties with solving related rates problems in calculus. In an effort to generate a resource that could potentially address some of these difficulties from a teaching standpoint, a questionnaire about effective instructional approaches related to the teaching of related rates problems, among other things, was administered to 14 veteran calculus instructors. Analysis of the responses provided by the instructors revealed that all the instructors considered the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Motivated by the scarcity of research that specifically addresses effective instructional approaches related to the concept of the derivative, the current study reports on veteran calculus instructors' perspectives on effective instructional approaches and educational technologies related to the teaching of the concept of the derivative in calculus. On a related note, a recent study (Mkhatshwa, 2023b) investigated experts' views regarding effective teaching approaches in the context of related rates problems in calculus. This study found that using diagrams during classroom instruction could be helpful in supporting students' reasoning about rate quantities that could be represented by derivatives when working with this type of problems.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the scarcity of research that specifically addresses effective instructional approaches related to the concept of the derivative, the current study reports on veteran calculus instructors' perspectives on effective instructional approaches and educational technologies related to the teaching of the concept of the derivative in calculus. On a related note, a recent study (Mkhatshwa, 2023b) investigated experts' views regarding effective teaching approaches in the context of related rates problems in calculus. This study found that using diagrams during classroom instruction could be helpful in supporting students' reasoning about rate quantities that could be represented by derivatives when working with this type of problems.…”
Section: Introductionmentioning
confidence: 99%